1976
DOI: 10.1051/animres:19760208
|View full text |Cite
|
Sign up to set email alerts
|

Production De Chevreaux Lourds. I. — Influence De l'ÂGE Et Du Mode De Sevrage Sur Les Performaxces Des Chevreaux Abattus a 26,5-29 Kg

Abstract: Une première expérience a été réalisée pour estimer l'intérêt de produire des chevreaux Iourds abattus à ioo-i2o jours. Vingt-quatre chevreaux mâles de race Alpine sont répartis en 3 lots. partir du 7 C jour, ils reçoivent tous individuellement 2 repas de lait de remplacement à une température de 6 à T 2 0e, du foin de pré, du maïs comprimé et un aliment concentré. Le lot P est sevré brutalement à 3 semaines, le lot L progressivement de 3 à 7 semaines et le lot T brutalement à scmaines. Ils sont abattus entre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

1976
1976
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…In the full model, females lost their advantage after weaning, which means that male kids may be more resistant to the stress of weaning. In contrast, FEHR and SAUVANT (1976) reported that females were more resistant to weaning stress. Heavy kids had steeper growth curves than light kids before weaning (P < 0.01) while the differences were lost after weaning (P > 0.05).…”
Section: Repeated Statement Analysesmentioning
confidence: 90%
“…In the full model, females lost their advantage after weaning, which means that male kids may be more resistant to the stress of weaning. In contrast, FEHR and SAUVANT (1976) reported that females were more resistant to weaning stress. Heavy kids had steeper growth curves than light kids before weaning (P < 0.01) while the differences were lost after weaning (P > 0.05).…”
Section: Repeated Statement Analysesmentioning
confidence: 90%
“…(Fehr, 1972 ;Fehr et Sauvant, 1976 (Ballard et Oliver, 1965 ;Bartley, Freedland et Black, 1966) ou le sevrage (Howarth, Baldwin et Ronning, 1968). En revanche, dans le tissu adipeux, l'adaptation du métabolisme lipidique en relation avec la croissance et le développement des fonctions digestives du rumen n'a été que partiellement abordée chez les jeunes ruminants (Howarth, Baldwin et Ronning, 1968 ; MorandFehr, 1985 .…”
unclassified